FarmAgriPoliS: An agricultural business management game for behavioral experiments, teaching, and gaming - Franziska Appel; Alfons Balmann; Changxing Dong; Jens Rommel (Leibniz Institute of Agricultural Development in Transition Economies (IAMO), 2018)
Business management games have been used for decades, primarily for educational purposes, training, and entertainment. More recently, the use of such games has expanded to an experimental platform. Usually business management games are directly designed and developed for one or more of these purposes; however, this paper discusses another possibility: the development of a business management game based on an existing agent-based model. We encourage this use and describe the extension of the agent-based model AgriPoliS, which has been widely used to analyze structural change in agriculture. We document the resulting software FarmAgriPoliS and provide a systematic classification of FarmAgriPoliS into the framework of business management games with agricultural background. Furthermore, we evaluate the suitability of FarmAgriPoliS for teaching, experimental use, and online gaming.
urn:nbn:de:gbv:3:2-90163
Keywords: 330; Business Management Game; Agent-Based Model; Behavioral Experiments; Agriculture; Teaching